Unmet need for family planning among eligible couples in urban slums of Prayagraj District, Uttar Pradesh, India - Setu, Yachna; Prakash, Shiv; Parveen, Khurshid; Singh, Richa (International Journal Of Community Medicine And Public Health, 2020)
Background: Unmet need for family planning is the major problem in developing countries. The use of family planning methods is better in urban areas as compared to rural areas and it is worse in urban slums. Thus unmet need for family planning is more in urban slums. Aims and objectives: To find out the prevalence of unmet need and to estimate the factors associated with unmet need for Family Planning. Methods: A community based cross sectional study was carried out on eligible couples selected from urban slums of Allahabad district by multistage random sampling and were interviewed by using pre-tested schedule. Data analysis was done by using SPSS version 21. Results: The study revealed that 22.47% (80/356) of eligible couples had unmet need for family planning. The most common reason for unmet need was irregular supply of family planning methods (31.25%), followed by opposition from husband/family members (21.25%), fear of side effects of using any family planning methods (17.25%), lack of knowledge regarding any family planning methods (13.75%). The unmet need for family planning was found to be associated with number of live births, education of female participants and occupation of male participants. Conclusions: The unmet need for family planning is high in slums areas and to improve the condition awareness should be created.